Cloning and expression of the spike protein of nephropathogenic infectious bronchitis virus strain MH5365/95 - Yap, May Ling (2004)
Infectious bronchitis is a highly contagious respiratory and kidney disease of poultry. The etiological agent, the prototype coronavirus, infectious bronchitis virus (IBV) is a member of the family Coronaviridae. The objective of this research is to isolate S1 protein from nephropathogenic IBV strain MH5365/95. The spike (S1) gene encodes for the S1 surface glycoprotein which is involved in virus attachment and infectivity. In addition, the S1 possesses the main immunological determinants essential for immune response and host protection. Production and isolation of the S1 protein from the rest of viral immunogens is necessary for further subunit vaccine development and protein structure-functional studies. To achieve these, therefore, the S1 gene of the IBV strain MH5365/95 was cloned into Escherichia coli expression system and also into the Baculovirus Expression Vector System (BEVS). This is the first study ever conducted in Malaysia in which the viral immunogen of a local IBV strain was cloned and expressed as a recombinant protein in heterologous cell system. The 1.75 kb S1 gene was amplified from the viral genomic RNA by RT-PCR method. It was cloned into the E. coli expression vector, pGEX-2T, and the baculovirus transfer vector, pAcG-2T. The recombinant clones were verified by restriction enzyme analysis, PCR and partial DNA sequencing. The recombinant S1 was expressed as glutathione S-transferase (GST) fusion protein in both the expression systems. In E. coli cells, the GST-S1 fusion protein was expressed at a relatively low level despite the optimization studies done. In Western blot analysis using an anti-GST polyclonal antibody, the E. coli-derived fusion protein was identified as a protein band having a molecular weight of approximately 90 kDa. Upon co-transfection of the recombinant baculovirus transfer vector with BaculoGold® linearized baculovirus genomic DNA in Sf9 insect cells, a viable recombinant baculovirus AcNPV (recS1-AcNPV) was verified by PCR and purified through plaque assay. The recS1-AcNPV recombinant baculovirus failed to produce any occlusion bodies in Sf9 cells consequent upon the replacement of baculoviral polyhedrin gene by S1 gene. In western blot analysis, the Sf9-derived GST-S1 fusion protein was identified as a protein band with molecular weight of approximately 105 kDa, reacting with anti-GST polyclonal antibody. The size of the S1 moiety was estimated to be approximately 79 kDa. This result showed that level of glycosylation in the Sf9-derived S1 protein was not equal to that of the authentic S1 glycoprotein. Moreover, the same protein was unable to react with the polyclonal antiserum raised against IBV MH5365/95. Thus, further analysis on the glycosylation pattern, conformation and antigenicity of the S1 protein is necessary.